Activin A alleviates neuronal injury through inhibiting cGAS-STING-mediated autophagy in mice with ischemic stroke. Issue 5 (May 2023) - Liu, Meilian; Li, Yudie; Han, Song; Wang, Hongyu; Li, Junfa
Activin A plays an essential role in ischemic stroke as a well-known neuroprotective factor. We previously reported that Activin A could promote white matter remyelination. However, the exact molecular mechanism of Activin A in neuronal protection post-stroke is still unclear. In this study, the middle cerebral artery occlusion/reperfusion (MCAO/R)-induced ischemic stroke mouse model and oxygen-glucose deprivation/reoxygenation (OGD/R)-treated primary neurons were used to explore the molecular mechanism of Activin A-mediated neuroprotection against ischemic injuries. We found that Activin A significantly inhibits cGAS-STING-mediated excessive autophagy through the PI3K-PKB pathway, but not mTOR-dependent autophagy. Consequently, Activin A protected neurons against OGD/R-induced ischemic injury and improved cell survival in a dose-dependent manner. In addition, Activin A improved neurological functions and reduced infarct size of mice with MCAO/R-induced ischemic stroke by inhibiting autophagy. Furthermore, Activin A depended on ACVR1C receptor to exert neuroprotective effects in 1 h MCAO/R treated mice. Our findings showed that Activin A alleviated neuronal ischemic injury through inhibiting cGAS-STING-mediated excessive autophagy in mice with ischemic stroke, which may suggest a potential therapeutic target for ischemic stroke.